MOTORWAY PATROL ON SLOVAK MOTORWAYS AND EXPRESSWAYS (Perner's Contacts, 2016)
Ensuring the motorways and expressways in terms of their safety is the primary task of the administrator. This activity includes, inter alia, on the one hand control of such roads, and on the other, to help drivers in need and deficiencies found. In Slovakia, the activity is performed by the National Motorway Company establishing Motorway patrols. The patrol operates 24 hours a day and has become a significant contribution to improving road safety in the Slovak Republic.
Keywords: application; traffic; motorway; communications; control; need; help; vehicle